2017
DOI: 10.2135/cropsci2016.09.0816
|View full text |Cite
|
Sign up to set email alerts
|

Seed‐Parent Fecundity Distributions in Bee‐Pollinated Forage Legume Polycrosses

Abstract: Abbreviations: Pf i , seed-parent fecundity frequency; SMOVC, polycross size standardized magnitude ordered value continuum; SPF, polycross size standardized Pf i .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The uneven pollen‐parent fecundity distribution in our trial corresponds to Riday, Reisen, Raasch, Santa‐Martinez, and Brunet () and Riday () who found that pollen‐parent fecundity distributions are uneven in polycrosses with most forage Legumes. The distribution in the present study could be somewhat biased due to the lower success rate of assigning parentage thus making certain pollen‐parents more likely to be identified based on rare SSR alleles.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The uneven pollen‐parent fecundity distribution in our trial corresponds to Riday, Reisen, Raasch, Santa‐Martinez, and Brunet () and Riday () who found that pollen‐parent fecundity distributions are uneven in polycrosses with most forage Legumes. The distribution in the present study could be somewhat biased due to the lower success rate of assigning parentage thus making certain pollen‐parents more likely to be identified based on rare SSR alleles.…”
Section: Discussionsupporting
confidence: 84%
“…The uneven pollen-parent fecundity distribution in our trial corresponds to Riday, Reisen, Raasch, Santa-Martinez, and Brunet TA B L E 3 Seed yield of progeny plants with high seed-yielding mothers and either a high seed-yielding father (marker-selected progeny) after cross-pollination and self-fertilization (if present), or a random father (traditionally selected progeny) (2015) and Riday (2017) who found that pollen-parent fecundity distributions are uneven in polycrosses with most forage Legumes.…”
Section: Marker-assisted Parentage Analysis Successfully Identifiedmentioning
confidence: 75%
“…1). Riday (2017) also observed preliminary evidence that seed‐parent and pollen‐parent fecundity distributions λ‐values were correlated. In this study sampling a larger number of polycrosses, we definitively observe that seed‐ and pollen‐parent fecundity distributions λ‐values are positively correlated.…”
Section: Discussionmentioning
confidence: 73%
“…1). The λ‐values 0.7 to 2.0 represent the 95th percentile observed by Riday (2017). Finally 1.2 was the median expected fecundity distribution λ‐value (Fig.…”
mentioning
confidence: 90%
See 1 more Smart Citation